SALT PRODUCTION IN GHANA - FIATI, PRO. PATRICK; TETTEH, FRANK (International Journal of Multidisciplinary Research and Studies, 2019)
Ghana has abundant salt deposits but is unable to satisfy West African demand let alone successfully compete with global producers. Known as ‘white gold, salt is one of the most common minerals on the planet and throughout history has served as an important foundation of civilization. Its importance cannot be overstated as there are about 14,000 documented benefits of salt, both medicinal and industrial. Salt deposits are inexhaustible but the demand is enormous and currently outstrips supply. About 100 countries in the world produce refined salt. From Alaska to Tierra del Fuego, the Americas produce almost as much salt as the rest of the world combined. The US is the leading global producer thanks to the Great Salt Lakes. It is responsible for 22 percent of the total world production capacity. Salt production in Ghana started in the 19th century and, aside from fishing, it is the major economic activity of people along its 500km coastline. The salt-producing areas in Ghana include the Keta lagoon, the Songhor lagoon, the Densu Delta area, the Nyanya lagoon, the Oyibi lagoon, the Amisa lagoon, Benyah lagoon.